ANALYSIS OF MENTAL DEVELOPMENT IN OLD AGE. - Xudayberdiyeva Svetlana Vladimirovna (TADQIQOTLAR.UZ, 2023)
Annotation: This article describes the mental analysis of development in old age. Such as old or pre-retirement age, retirement period and the first years after retirement, period of age, long-term living in conditions of sharp deterioration of health, long-term stay with relatively good health.